MODEL-MODEL MANAJEMEN PERUBAHAN PENDIDIKAN ISLAM TRANSFORMATIF - Imro'atus Solikah; Binti Maunah; Asrop Safi’i (STAI KH. Muhammad Ali Shodiq, 2024)
Abstract. This study aims to identify and analyze change management models in the context of transformative Islamic education. In the era of globalization and technological development, Islamic educational institutions face demands to adapt and undergo fundamental changes in management and teaching methods. This research employs the library research method by analyzing various literatures related to applicable and relevant change management models in Islamic education. The findings show that Lewin’s Change Management, Kotter’s 8-Step Change Model, and the ADKAR model are effective approaches to assist Islamic educational institutions in the change process. Each model emphasizes organizational and individual readiness for change and strengthens the commitment to maintaining long-term results. Furthermore, this study highlights that the application of these models significantly impacts the development of Islamic educational institutions, making them more responsive to modern changes while maintaining core religious values. This research is expected to provide guidance for Islamic educational managers in designing adaptive and transformative change management strategies. Keywords: Model; Change Management; Islamic Education; Transformative